2013
DOI: 10.1016/j.virol.2013.07.033
|View full text |Cite
|
Sign up to set email alerts
|

The charged residues in the surface-exposed C-terminus of the Soybean mosaic virus coat protein are critical for cell-to-cell movement

Abstract: The Soybean mosaic virus (SMV) coat protein (CP) is necessary for virion assembly and viral cell-to-cell and long-distance movements in plants. We previously showed that the C-terminal region of the SMV CP is required for CP self-interaction. In the present study, we generated SMV mutants containing CPs with single amino acid substitutions of the charged amino acids in the C-proximal region. Infectivity and cell-to-cell movement of the SMV mutants were examined in soybean plants. Through this genetic approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…We previously developed a useful viral vector system by engineering SMV-G7H to express foreign genes in soybean and by tagging the SMV vector with a GUS gene; using this system, we were able to visualize virus infection and movement in plant cells2728. The same strategy was used to tag SMV-G5H with GUS (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously developed a useful viral vector system by engineering SMV-G7H to express foreign genes in soybean and by tagging the SMV vector with a GUS gene; using this system, we were able to visualize virus infection and movement in plant cells2728. The same strategy was used to tag SMV-G5H with GUS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting construct with the GmPP2C3a insert in the correct orientation was named pSMV-G7H-GmPP2C3a. The same strategy was used to construct SMV-G5H-based viral vector carrying the cloning sites ( Xba I and Mlu I) between P1 and HC-Pro as described previously28, and the amplified GUS gene was inserted into the XbaI site to generate pSMV-G5H-GUS as described previously27. For simultaneous expression of GUS and GmPP2C3a, an additional NIa-Pro cleavage site and the cloning sites ( Sal I and Sna BI) were engineered into the polyprotein ORF between the Nib and CP cistrons of pSMV-G7H-GUS as described previously47; the resulting construct was named pSMV-G7H-GUS-MCS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations introduced into the core domain of the potyvirus Tobacco etch virus CP result in the inability of the protein to form virions and virus incompetence for cell-to cell-movement, whereas deletions in either the N-or C-terminal CP regions, which are dispensable for virion formation, do not abolish viral cell-to-cell movement, although they do make it slower compared with the wildtype virus (Dolja et al, 1994(Dolja et al, , 1995. In a similar manner, point mutations in the CP C-terminal region of Soybean mosaic virus, another potyvirus, block both virion formation and viral cell-to cell movement (Seo et al, 2013), indicating a direct link between them. Furthermore, immuno-gold labelling and electron microscopy studies have revealed the potyvirus CP in plasmodesmal cavities Rodríguez-Cerezo et al, 1997), and its localization within plasmodesmata often correlates with the presence of CPcontaining fibrillar material, with the dimensions of fibrils similar to the virion diameter .…”
Section: Role Of Virions In Cell-to-cell Transport Of Filamentous Virmentioning
confidence: 99%
“…Potyviral capsid proteins (CPs) not only form the viral particle but also participate in cell-to-cell and systemic movement (6,7). The variable N-and C-terminal regions of the CPs exposed on the virion surface are required for long-distance transport, are involved in aphid transmission (DAG motif), and may also assist in cell-to-cell spreading (7)(8)(9)(10), whereas the conserved core regions of CPs are necessary for virion assembly and the cell-to-cell movement of potyviruses (6,7).…”
mentioning
confidence: 99%